Exploring the Role of Female Auditors in Audit Judgement - Ni Gusti Ayu Ellsa Damayanti; Muhammad Ansar (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2025)
This study is to determine the Role of Female Auditors in Audit Judgment at the Inspectorate of Central Sulawesi Province. This type of research is qualitative with a phenomenological approach. The data collection techniques used were direct interviews and documentation, with a total of 7 sources. The data analysis technique in this research is an interactive analysis model with stages, namely Data Collection, Data Reduction, Data Presentation, Conclusion Drawing, and Theory Relevance. Audit Experience, Audit when Planning, Task Complexity are the main indicators in the Role of Female Auditors in Audit Judgment. The results of this study indicate that experience is very important in audit judgment, task complexity is given to auditors who are considered to have more experience in their fields, the tasks of female auditors when planning have no difference or are equivalent to male auditors, and there is no specific role by female auditors in audit judgment so that the tasks assigned to auditors are not influenced by gender but rather by the abilities and experience of the auditors themselves.